CRITERIA FOR DESTABILIZATION OF THE DISEASE COURSE IN PATIENTS WITH CORONARY HEART DISEASE - Romanova, V.O.; Kuzminova, N.V.; Ivankova, A.V.; Lozinsky, S.E.; Kniazkova, I.I.; Poberezhets, O.L.; Shkarovskyi, Yu.L. (World of Medicine and Biology, 2023)
173 patients with various coronary heart disease course variants were examined to identify possible pathogenetically based criteria for destabilization of the disease course. It was established that patients with an unstable course of coronary heart disease were characterized by both more pronounced inflammatory reaction and impairment of vascular endothelial function. Inflammatory activation was evidenced by a significant increase in biochemical markers of inflammation: high-sensitivity C-reactive protein and tumor necrosis factor-α – not only relative to the control group, but also to patients with stable coronary artery disease. The same differences were observed about endothelial dysfunction that was evidenced by a significant increase in its biochemical markers (ET-1, sVCAM, and PAPP-A). Therefore, such markers can be considered as criteria for destabilizing of the atherosclerotic process.
Keywords: coronary heart disease; nonspecific systemic inflammation; endothelial dysfunction; hyperleptinemia; dyslipidemia